Pengaruh Metode Pembelajaran Drill terhadap Peningkatan Hasil Belajar Matematika Siswa Kelas IV SD Negeri 2 Muara Aman - Zamratul Aini (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
Background: Mathematics is a very important subject to study. Mathematics lessons include the development and use of concepts such as numbers, formulas, geometry, and algebra to understand and explain phenomena in various contexts. To improve the quality of students' mathematics learning, it is necessary to develop material through a learning method which is expected to improve students' abilities in solving mathematical problems. Method: The research design is "Pre-Experimental Whithout Control Group Design". The population in this study was the fourth grade students of SD Negeri 2 Muara Aman, totaling 25 people. The sampling technique in this study used a total sampling technique where the entire population was sampled, namely 25 people. The results of this research were analyzed using the Paired t-test using SPSS 22 software. Results: The average mathematics score of respondents increased after being given the intervention by 51.13. Result: The results of the Paired T Test showed a p value of 0.000< α=0.05. Conclusion: The conclusion of this research is that there is an influence of the drill method on improving mathematics learning outcomes for fourth grade students at SD Negeri 2 Muara Aman in 2023. It is hoped that the results of this research will become a reference for teachers in developing effective learning methods to increase students' motivation and enthusiasm in learning interesting mathematics subjects. positive impact on increasing elementary school student learning achievement.